2015 International Conference on Information and Communication Technology Research (ICTRC) 2015
DOI: 10.1109/ictrc.2015.7156437
|View full text |Cite
|
Sign up to set email alerts
|

Differential distributed space-time coding for vehicle-to-vehicle networks

Abstract: Differential distributed space-time coding (DDSTC) has been proved to be suitable for wireless relay networks, since it can provide spatial diversity without the need for channel state information at neither the transmitter nor the receiver side. However, DDSTC suffers from significant error floor in fast-fading channel conditions with high Doppler frequencies due to rapid time variations. For this reason, multiple-symbol differential detection (MSDD) has been proposed in the past, where the detection process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The first-hop is not coherent while the second-hop is coherent. In [16], the performance of a differential distributed space-time coding scheme was investigated for vehicle-to-vehicle networks employing low-complexity multiplesymbol differential detection for low, medium, and fast fading channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-hop is not coherent while the second-hop is coherent. In [16], the performance of a differential distributed space-time coding scheme was investigated for vehicle-to-vehicle networks employing low-complexity multiplesymbol differential detection for low, medium, and fast fading channels.…”
Section: Introductionmentioning
confidence: 99%
“…authors independently suggested differential encoding/decoding for wireless relay networks in [11][12][13][14][15][16]. The authors of [11] presented a general approach for DDSTC and they also provided a few code constructions.…”
mentioning
confidence: 99%